Mandailing Islamic Law Views on the Manangko Boru Tradition in Mandailing Customs - Nst, Yurizka Syahdani (El-Sirry: Jurnal Hukum Islam dan Sosial, 2024)
Manangko Boru is a tradition where a woman who is still single or who has been proposed is taken by a man to her parents' house secretly to be his wife or also known as marlojong. There are two types of manangko boru, namely manangko boru for women who are still young or single and manangko boru who has been married by someone else. The purpose of this research is to find out how Islamic law views customs and traditions that run in social life, especially in the aspect of marriage, namely this manangko boru tradition. The data obtained to obtain information about the applicable traditions and customs was carried out by the observation and interview method of the perpetrators of the manangko boru tradition, traditional figures, religious figures and community figures in South Panyabungan District. With the results of the research, it is known that in customs, it is actually not justified to maintain the manangko boru tradition because the customs that run in social life are also based on Islam so that what is not justified in Islam is also not justified in Mandailing customs. And according to Islamic law, it is also not justified to maintain this tradition because it violates the rules and is not in line with Islamic law.